2017
DOI: 10.1371/journal.pbio.2001930
|View full text |Cite
|
Sign up to set email alerts
|

MAIT cells launch a rapid, robust and distinct hyperinflammatory response to bacterial superantigens and quickly acquire an anergic phenotype that impedes their cognate antimicrobial function: Defining a novel mechanism of superantigen-induced immunopathology and immunosuppression

Abstract: Superantigens (SAgs) are potent exotoxins secreted by Staphylococcus aureus and Streptococcus pyogenes. They target a large fraction of T cell pools to set in motion a “cytokine storm” with severe and sometimes life-threatening consequences typically encountered in toxic shock syndrome (TSS). Given the rapidity with which TSS develops, designing timely and truly targeted therapies for this syndrome requires identification of key mediators of the cytokine storm’s initial wave. Equally important, early host resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 67 publications
11
147
1
Order By: Relevance
“…Mucosa‐associated invariant T (MAIT) cells have come under increasing scrutiny in recent years. They may fulfill protective or pathogenic functions in infectious diseases and malignancies . MAIT cells are best known for their immunomodulatory cytokine production capacity.…”
Section: Preamblementioning
confidence: 99%
See 1 more Smart Citation
“…Mucosa‐associated invariant T (MAIT) cells have come under increasing scrutiny in recent years. They may fulfill protective or pathogenic functions in infectious diseases and malignancies . MAIT cells are best known for their immunomodulatory cytokine production capacity.…”
Section: Preamblementioning
confidence: 99%
“…MAIT cells constitutively express several cytokine receptor components such as CD127 (IL‐7Rα), CD212 (IL‐12Rβ1), CD218a (IL‐18Rα), and CD218b (IL‐18Rβ) . Therefore, acting alone or in additive/synergistic combinations, IL‐2, IL‐7, IL‐12, IL‐15, IL‐18, IFN‐α, and IFN‐β can promote robust inflammatory and/or cytotoxic responses by MAIT cells .…”
Section: Mait Cells In Briefmentioning
confidence: 99%
“…The differentiation required MAIT cell-dependent production of GM-CSF, and the role of IL-12 or IL-18 in MAIT cell activation was not investigated. Shaler et al have demonstrated another MR1-independent pathway for MAIT cell activation through bacterial superantigens 24 . Overall, given the localization of MAIT cells at common sites of infection, both MR1-independent and MR1-dependent MAIT cell activity is likely to play a role in defense against certain infections in vivo .…”
Section: Mr1-restricted T Cell Responses To Bacteria and Fungimentioning
confidence: 99%
“…It has been widely observed that they produce the pro-inflammatory cytokines IFN-γ and TNF-α 48,10,24,38,62,63 . MAIT cell effector function in response to TCR signaling is triggered more rapidly than conventional T cells.…”
Section: Mechanisms By Which Mait Cells Influence Immunity To Bacterimentioning
confidence: 99%
“…Mucosal‐associated invariant T (MAIT) cells are innate‐like T cells that play a role in the antibacterial and antifungal response by recognizing riboflavin metabolites produced by these organisms 9 . MAIT cells comprise 0.1% to 10% of the circulating T‐cell population, 10 are abundant in the liver, lungs, intestine, stomach, kidney, and the female genital mucosa 11–15 and can respond rapidly, that is, within hours, to a wide range of bacteria 16,17 . MAIT cells are characterized by the expression of the semi‐invariant Vα7.2‐Jα12/20/33 chain as a part of their T‐cell receptor (TCR).…”
Section: Introductionmentioning
confidence: 99%